Isolation, Selection and Antimicrobial Activity of Actinomycetes from Mangrove Soil of Can Gio Forest, Hochiminh City, Vietnam (Global Journal of Science Frontier Research, 2021)
The Can Gio Mangrove is a Biosphere Reserve of UNESCO since 2000 and it is also a well-known example of "mangrove afforestation and reforestation area". A total of 63 actinomycetes were isolated from 25 samples of 9 different sites in mangrove forest soil Can Gio, HoChiMinh city, Vietnam. Almost their colonies have round-shaped; milky, white clear and yellow, entire or loabate margin; diameter size of these colonies varied from 0.2 to 3.0 mm. Twenty-nine of 63 tested isolates could produce antimicrobial active metabolites inhibiting at least one of the tested pathogens and 9 isolates were selected for 16S rDNA sequencing. The result showed that genus Streptomyces (8 isolates) and other genera including 1 isolates were Gram-negative bacteria (Stenotrophomonas). The antimicrobial activity and the amplifying genes coding for polyketide synthetase (PKS) and nonribosomal peptide synthetase (NRPS) showed that 8 strains had broad-spectrum antimicrobial activity, mainly against gram-positive bacteria as Bacillus cereus and Staphylococcus aureus.
Keywords: actinobacteria; antimicrobial activity; bacteria references; can gio; mangrove forest soil